Sociolinguistic Analysis of The Dialogue Between Prophet Ibrahim and His Father: Speech Acts and Speaker Variation in The Qur'an - Fakhrurrozi, Fakhrurrozi; Nasrulloh, Nasrulloh; Syuhadak, Syuhadak; Munawaroh, Azizatul (J-LELC: Journal of Language Education, Linguistics, and Culture, 2025)
The dialogue of Prophet Ibrahim to his father in QS Maryam: 42-45 not only contains the message of da'wah tawhid, but also reflects a very subtle and contextual communication strategy. This phenomenon is interesting to study academically because it shows that the Qur'an forms a rich pattern of social communication. This study aims to examine the form of language variation and speech acts in the dialog with a sociolinguistic approach. This qualitative research uses the method of literature study and thematic analysis of relevant verses, supported by the theory of language variation (idiolect, dialect, chronolect, sociolect) and the theory of speech acts of Austin and Searle. The results show that Prophet Ibrahim's language style reflects the depth of wisdom and subtlety of character in preaching to the closest people. The speech acts used are persuasive and contemplative, which linguistically indicates an attempt to encourage critical thinking and self-awareness in the interlocutor. In addition, significant differences were found between classical Arabic used in the Qur'ān and modern Arabic, especially in aspects of morphology and sentence structure, reflecting chronolectal variation. This study recommends expanding the linguistic approach in Qur'anic studies to understand the dynamics of da'wah communication more contextually and deeply. The significant contribution of this study lies in its ability to bridge the linguistic approach with exegetical analysis, providing a holistic understanding of da'wah communication strategies in a rich Qur'anic context.